Projection: A Communally-Intuited Approach of Nepali People in Mitigating Anxiety - Ghimire, Rishiram (Journal of Nepalese Studies, 2025)
This article focuses on the psychological aspect of Nepali people who are successful in managing psychogenic problems like anxiety and frustration. Anxiety and frustration are the product of disturbing emotions when they do not get proper outlet from the human psyche. As long as these two problems persists in a person, their daily behaviors deviate and impact personal as well as public affairs. These two problems are known as mental disorder and keeping them in control is quite necessary in this acquisitive society. However, these two disorders are not limited to covetousness, they are associated with the life-style of a person that is guided by the environment they are living in. The researcher, while conducting research on this topic, exerts ‘psychoanalysis’ as a theoretical framework and concerned theorist Sigmund Freud and psychological insights help in finalizing this work. Eventually, this work helps find answer to the question ‘why Nepalese people are less prone to anxiety-based problems and emotional deviation in comparison to the people from industrialized and technocratic society’. Projection, though Nepali people do not know what it means, is helping them deal with psychogenic problems like anxiety, frustration, distress, despair, melancholy, and other emotional disorders. Since projection is a way for the ego of a person to defend itself against anxiety or internal conflict of emotions by expressing the source of distress, a person, through projection, unknowingly attributes their own unacceptable thoughts, feeling or impulses to someone else. In this process, the speaker sees him/her in others and consoles himself/herself as a good figure.